Integrating environmental sustainability into hospitals performance management systems: a scoping review - Michele Dolcini; Francesca Ferrè; Andrea Brambilla; Stefano Capolongo (BMC Health Services Research)
Abstract Introduction Among the healthcare sector, hospitals are the most resource-intensive infrastructures, contributing significantly to environmental degradation. As global sustainability imperatives intensify, there is a critical need to integrate environmental sustainability into hospital performance measurement systems. The study objective is to highlight the most recurrent environmental performance for hospital sustainability from the recent scientific literature and identify key performance indicators. Methods This study employs a scoping review methodology to analyze peer-reviewed recent publications addressing environmental sustainability performance measurement and management in hospitals. The literature search was performed using PubMed, Web of Science and Scopus databases. The search was limited to papers published from 2009. The initial searches resulted in 545 studies. The final sample included 22 papers. Results The review identifies 6 key sustainability domains: energy management, waste management, water consumption, greenhouse gases emissions, transportation and mobility, and site sustainability. The results underscore the multidimensional nature of environmental performance in healthcare facilities and reveal significant variability in the scope and specificity of existing metrics across studies. Discussion The findings are synthesized to propose a unified, indicator-based environmental sustainability assessment framework for hospitals with a set of 18 environmental key performance indicators (EKPIs). The results underscore the multidimensional nature of environmental performance in healthcare facilities and reveal significant variability in the scope of existing metrics across studies. The findings highlight the necessity of integrating standardized indicators into hospital performance assessment frameworks to ensure comparability, track progress, and drive improvements. Additionally, the lack of harmonized measurement systems poses challenges for benchmarking and scaling sustainable practices across diverse healthcare settings. Conclusion This study contributes to the ongoing debate on sustainable healthcare by proposing a structured framework of EKPIs based on the most recent scientific literature and tailored to hospital environments. The framework offers hospital administrators and policymakers actionable tools to monitor and enhance environmental performance.